C-Terminal Anchoring of mid1p to Membranes Stabilizes Cytokinetic Ring Position in Early Mitosis in Fission Yeast - Celton-Morizur, Séverine (American Society for Microbiology, 2004)
mid1p is a key factor for the central positioning of the cytokinetic ring in Schizosaccharomyces pombe. In interphase and early mitosis, mid1p forms a medial cortical band overlying the nucleus, which may represent a landmark for cytokinetic ring assembly. It compacts before anaphase into a tight ring with other cytokinetic ring components. We show here that mid1p binds to the medial cortex by at least two independent means. First, mid1p C-terminus association with the cortex requires a putative amphipathic helix adjacent to mid1p nuclear localization sequence (NLS), which is predicted to insert directly into the lipid bilayer. This association is stabilized by the polybasic NLS. mid1p mutated within the helix and the NLS forms abnormal filaments in early mitosis that are not properly anchored to the medial cortex. Misplaced rings assemble in late mitosis, indicating that mid1p C-terminus binding to membranes stabilizes cytokinetic ring position. Second, the N terminus of mid1p has the ability to associate faintly with the medial cortex and is sufficient to form tight rings. In addition, we show that mid1p oligomerizes. We propose that membrane-bound oligomers of mid1p assemble recruitment “platforms” for cytokinetic ring components at the medial cortex and stabilize the ring position during its compaction.